SER MULHER SEGUNDO CLARICE LISPECTOR: UMA APRENDIZAGEM ENTRE JORNALISMO E LITERATURA - De Crescenzo, Luigia (Cultura Latinoamericana, 2021)
This study aims to analyse the way in which Clarice Lispector developed her reflection on the condition of women through literary and journalistic writing. Although she has constantly rejected the label of feminist, the works of the Brazilian writer seems to trace a path of liberation from social standards: an apprenticeship of “being a woman” that dispenses with any concept of gender. Referring mainly to the reflections of Judith Butler and Pierre Bourdieu, this aspect will be deepened through the analysis of the “women’s pages” published under pseudonyms between the 50s and the 60s, and the novel An apprenticeship or the book of pleasures; texts that are very different from each other but that offer interesting perspectives on “being a woman” according to Clarice Lispector.